Modeling and control simulation of an unmanned aerial vehicle with multi-axisymmetric thrust vectoring nozzles - Quek, Jian Xing (2018)
New breeds of high altitude vehicles are pushing the air traffic altitude boundary for higher flight efficiency and the atmospheric environment at higher altitudes will become thinner until it reaches the inoperable flight regime of traditional propeller and air breathing jet propulsion. Thrust Vectoring Control (TVC) is one of the means of flight control method for vehicles to operate in both the inoperable flight regime and normal atmosphere. To develop a simulation test bed for a highly dynamic Unmanned Aerial Vehicle (UAV) using TVC, a mathematical model similar to quadcopter was derived as it consists of four micro thrusters. Prototype was fabricated to ensure a realistic mathematical model. Linear quadratic controllers, namely the Linear Quadratic Regulator (LQR) and Linear Quadratic Integral (LQI), were designed for position control to track reference trajectory. For simplicity in testing the feasibility of the prototype and its controller, simulation was carried out in an indoor environment to remove disturbances. Literatures of cold gas thruster, similar vehicle system such as the lunar landers, types of thrust vectoring methods and controller designs for multicopter controller was reviewed. The design and fabrication of the prototype includes the sizing of the cold gas micro thruster, design of the gimbal platform and setting up the required electrical components. Lastly, the controllers were designed and the behavior of the model under the proposed controller was simulated with Simulink and Virtual Reality Modelling Language (VRML).